2020
DOI: 10.3389/fpsyg.2020.00658
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Social Networks and Physical, Verbal, and Indirect Aggression in China: The Moderating Role of Gender

Abstract: Aggressive adolescents are preferable in some Western cultures, whereas Confucianism places great emphasis on the inhibition of aggressive behaviors in Chinese culture. Using the longitudinal social network analysis, we used a sample of 1354 Chinese adolescents (54% boys, ages 12-15) who were followed over 1 year at three time points to examine the association between friendship dynamics and physical, verbal, and indirect aggression and the moderating role of gender. This study found the following: (1) Student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 87 publications
(219 reference statements)
0
6
0
Order By: Relevance
“…Boys’ transitions to stage II shows that puberty has started, and their thinking and generalization abilities and emotional regulation abilities gradually improve. 12 Studies have reported that good emotional regulation could help reduce the impact of anger on aggressive behavior. 1 It may also be that the improvement of boys’ abilities to control emotions in stage II leads to the change of the direct effects from the AAS to the VAS and the direct path from the PAS to the HAS.…”
Section: Discussionmentioning
confidence: 99%
“…Boys’ transitions to stage II shows that puberty has started, and their thinking and generalization abilities and emotional regulation abilities gradually improve. 12 Studies have reported that good emotional regulation could help reduce the impact of anger on aggressive behavior. 1 It may also be that the improvement of boys’ abilities to control emotions in stage II leads to the change of the direct effects from the AAS to the VAS and the direct path from the PAS to the HAS.…”
Section: Discussionmentioning
confidence: 99%
“…(Confucius and Legge, 2008). Confucianism, as the foundation for Chinese culture, places great emphasis on the importance of maintaining group wellbeing and harmony, whereas the self-interested nature of aggressive behaviors could potentially harm group stability and lead to individuals becoming loathed and rejected (Zhang et al, 2020), and this may lead Chinese students to be less likely to perform both prosocial and aggressive behavior. Thus, the failure to discover a bi-strategic group may not result from choosing different profiles' indicators but primarily be attributed to cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates and SEs for each effect parameter in the SIENA models for individual schools were then combined in a metaanalysis, using the multilevel network analysis method of Snijders and Baerveldt (2003). Previous studies using SIENA modeling to investigate the co-evolution of network ties and smoking behavior, and more recently published Stochastic Actor-Oriented Models have used similar meta-analytic procedures to combine estimates across different networks (Block, 2018;Hooijsma et al, 2020;la Roi et al, 2020;Leszczensky and Pink, 2020;Mercken et al, 2009Mercken et al, , 2012Windzio, 2021;Zhang et al, 2020). For each effect, the overall null hypothesis that the effect was 0 in all schools was tested using Fisher's combination of one-sided tests procedure with two onesided tests (Fisher, 1925;Hedges and Olkin, 1985).…”
Section: Methodsmentioning
confidence: 99%